ANALISIS PEMANFAATAN LAHAN DISTRIK FEF KABUPATEN TAMBRAUW SEBAGAI PUSAT PEMERINTAHAN - Purba, Gema; Mujiati; Siregar, Tiurlina (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
The background introduces Tambrauw Regency's formation and the need for a governmental center, specifically focusing on Fef District as per Indonesian law. The introduction also touches upon the administrative, strategic, and technical aspects that must be considered in selecting a capital. This section discusses theories related to location, spatial order, and urban functions, with references to prominent theories like those of Tarigan (2006) and Yunus (2005). It provides a foundational understanding of urban centers' roles and the criteria for selecting administrative capitals. The research employs documentation study methods, analyzing secondary data from relevant institutions, statistics, and legislation. The analytical approaches include Scalogram Analysis, SWOT Analysis, and Christaller's Central Place Theory, providing a multi-faceted examination of Fef District’s suitability. The Scalogram Analysis indicates that Fef ranks sixth in terms of infrastructure, suggesting that other districts may be better prepared as governmental centers. However, Christaller's theory highlights Fef's strategic location as a justification for its selection as the capital. The SWOT analysis outlines strengths, weaknesses, opportunities, and threats, emphasizing the need for accelerated development in Fef to support its role. While Fef's current infrastructure may not be fully adequate, its strategic location supports its potential as the governmental center. The paper suggests that careful planning and development are necessary to transform Fef into a functional capital for Tambrauw Regency.